The Plasma Channel Evolution Characteristics of Pulsed Flashlamps Working in an Array - 贾申利 李瑞 刘建军 李兴文 宋晓川 李海兵 (Plasma science & technology, 2013)
This work is devoted to the study of plasma channel evolution characteristics in pulsed xenon flashlamps working in an array. Influencing factors on the plasma channel evolution process are studied, including pre-ionization pulse and neighbor fiashlamps. It has been found that neighbor flaShlamps affect the plasma channel by shaping the electric potential distribution, rather than by Lorentz force. Branching is observed in the plasma channels of the flashlamps in the middle of the array. Inconsistency also exists in the plasma channels of these flashlamps in different tests. The branching and inconsistency are both caused by the unique electric field distribution in these flashlamps. Besides, the pre-ionization pulse can help the main pulse plasma channel to develop more smoothly and faster, which will weaken the shock wave and benefit the mechanical strength of the flashlamp.